Antecedents and Perceived Benefits of Religious Conversion—An Exploratory Study within a Protestant Congregation - Pop, Marian Rodion (Religions, 2024)
Religious conversion is a multifaceted phenomenon that has captivated scholars, theologians, and social scientists alike. With the aim of delineating and comprehending the variables associated with personal and social transformation, this paper employed an exploratory quantitative inquiry within a sample of participants affiliated with a Protestant church, chosen for its relevance to analogous experiences within worldwide congregations. The findings present antecedent factors that exert a favorable influence on the conversion process of parishioners, establishing a pronounced correlation between overall satisfaction and perceived benefits observed among regular church attendants. Antecedents to religious conversion are deeply rooted in a complex interplay of personal and social factors. Conversion paths are shaped by existential questioning, crises, or a search for meaning, with key roles played by social factors such as family, peers, and exposure to belief systems through preacher pressure. The benefits of religious conversion are equally multifaceted and can encompass various dimensions of an individual’s life. Spirituality often becomes a source of solace and resilience, helping individuals navigate adversity. On the emotional level, conversion may provide a sense of belonging, inner peace, and a framework for understanding the world and life’s challenges. Adopting a new faith enhances community support and is influenced by cultural and entertainment experiences, contributing to the decision to convert. However, understanding the antecedents and benefits of religious conversion offers valuable insights into the dynamics of faith and human transformation under the global challenges and guidance for religious marketing in the religious postmodern pluralism era. Further research is essential to examine the diverse experiences of religious conversion and their long-term impacts on well-being and societal cohesion, ultimately concluding that it is a multifaceted process influenced by numerous antecedents.